2016
DOI: 10.5114/cipp.2016.61757
|View full text |Cite
|
Sign up to set email alerts
|

Relations with parents and identity statuses in the relational domain in emerging adults

Abstract: Emerging adulthood is a core developmental period in which individuals can develop a meaningful identity in the relational domain (with a romantic partner). The aim of the study was to examine relationships between relations with parents and identity statuses in the relational domain in emerging adults. participants and procedureParticipants were 266 (47.30% males) emerging adults (M = 22.50, SD = 1.73). They completed self-report measures of relations with parents and identity. resultsMore than half of the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Although Poland has become more of an individualistic society in the recent few decades, it is still perceived as a traditional society with a strong value placed on family ( Zagórska et al, 2012 ). Emerging adults in Poland, in line with emerging adults in other Western countries, are strongly focused on their personal development and independence ( Zagórska & Lubieniecka, 2018 ; Michałek, 2016 ), but they are also involved in relationships and start taking responsibility for other people (such as taking care of their parents, volunteer work, etc.). The latest Eurostat (2020) report showed that young people are more willing to combine work and education, which allows them to attain more financial independence (the EU-27 employment rate in 2019 for young people aged 25-29 years was 74.6%).…”
Section: Discussionmentioning
confidence: 99%
“…Although Poland has become more of an individualistic society in the recent few decades, it is still perceived as a traditional society with a strong value placed on family ( Zagórska et al, 2012 ). Emerging adults in Poland, in line with emerging adults in other Western countries, are strongly focused on their personal development and independence ( Zagórska & Lubieniecka, 2018 ; Michałek, 2016 ), but they are also involved in relationships and start taking responsibility for other people (such as taking care of their parents, volunteer work, etc.). The latest Eurostat (2020) report showed that young people are more willing to combine work and education, which allows them to attain more financial independence (the EU-27 employment rate in 2019 for young people aged 25-29 years was 74.6%).…”
Section: Discussionmentioning
confidence: 99%